(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2010)
The study was designed to explore serum copper as a risk factor for coronary artery disease (CAD). In this case-control study 30 healthy controls and 60 diagnosed cases of acute myocardial infarction (AMI) were enrolled. Serum copper concentration and serum lipid profile were measured in all study subjects. Serum copper level was significantly higher in AMI as compared to controls. The concentrations of serum TC, TG, LDL-C level were found to be significantly higher in cases as compared to controls. The concentration serum HDL-C was found to be significantly lower in cases as compared to controls. CAD leads to raised serum copper level and it has positive correlation with TC, TG and LDL-C but negative correlation with HDL-C in males. Keywords: Coronary artery disease; serum copper; acute myocardial infarction; total cholesterol; triglyceride; low density lipoprotein cholesterol. DOI: 10.3329/bjpp.v24i1.5730 Bangladesh J Physiol Pharmacol 2008; 24(1&2) : 7-9